Alpha-thalassemia caused by a large (62 kb) deletion upstream of the human alpha globin gene cluster. - Hatton, C; Wilkie, A; Drysdale, H; Wood, W; Vickers, M; Sharpe, J; Ayyub, H; Pretorius, I; Buckle, V; Higgs, D (1990)
We describe a family in which alpha-thalassemia occurs in association with a deletion of 62 kilobases from a region upstream of the alpha globin genes. DNA sequence analysis has shown that the transcription units of both alpha genes downstream of this deletion are normal. Nevertheless, they fail to direct alpha globin synthesis in an interspecific hybrid containing the abnormal (alpha alpha)RA chromosome. It seems probable that previously unidentified positive regulatory sequences analogous to those detected in a corresponding position of the human beta globin cluster are removed by this deletion.